Links between sediment consolidation and Cascadia megathrust slip behaviour. Issue 12 (December 2017) - Han, Shuoshuo; Bangs, Nathan; Carbotte, Suzanne; Saffer, Demian; Gibson, James
Abstract At sediment-rich subduction zones, megathrust slip behaviour and forearc deformation are tightly linked to the physical properties and in situ stresses within underthrust and accreted sediments. Yet the role of sediment consolidation at the onset of subduction in controlling the downdip evolution and along-strike variation in megathrust fault properties and accretionary wedge structure is poorly known. Here we use controlled-source seismic data combined with ocean drilling data to constrain the sediment consolidation and in situ stress state near the deformation front of the Cascadia subduction zone. Offshore Washington where the megathrust is inferred to be strongly locked, we find over-consolidated sediments near the deformation front that are incorporated into a strong outer wedge, with little sediment subducted. These conditions are favourable for strain accumulation on the megathrust and potential earthquake rupture close to the trench. In contrast, offshore Central Oregon, a thick under-consolidated sediment sequence is subducting, and is probably associated with elevated pore fluid pressures on the megathrust in a region where reduced locking is inferred. Our results suggest that the consolidation state of the sediments near the deformation front is a key factor contributing to megathrust slip behaviour and its along-strike variation, and it may also have a significant role in the deformation style of the accretionary wedge. Consolidated sediments in the Cascadia subduction zone may create conditions favourable for megathrust earthquake ruptures over long distances and close to the trench, according to analyses of seismic velocity of sediments from the region. Less-consolidated sediments instead may promote aseismic slip of the plate boundary.